Employing the induced hypocrisy paradigm to encourage nutrition on college campuses - Schwartz, Sarah Ann (Kansas State University, 2009)
According to the Centers for Disease Control and Prevention, overweight and obesity rates in the United States continue to increase. And yet, despite their resources to encourage healthy lifestyles, college campuses reflect the national trend. Colleges and universities often utilize health campaign strategies such as social norms marketing and peer health education to encourage campus-wide health initiatives. However, based on an application of effective health communication attributes, both strategies demonstrate limitations that must be addressed in future collegiate health campaign approaches. I analyzed the effectiveness of adopting an induced hypocrisy health campaign to encourage nutrition. The induced hypocrisy paradigm has resulted in successful behavioral change by having participants create a pro-attitudinal message. Then, participants are reminded of their past failure to engage in the behaviors they advocated. It was hypothesized that hypocritical subjects would purchase more nutrition bars than subjects in any of the other conditions. The results indicate that, although more hypocritical subjects purchased more nutrition bars than subjects in the other conditions, the findings were not found to be statistically significant. Interpretations of the study findings as well as implications for future nutrition campaign initiatives are discussed.
Keywords: induced hypocrisy; nutrition; cognitive dissonance; health campaigns; Speech Communication (0459)